2014
DOI: 10.1177/2151458514560215
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Bone Mineral Density Following Acute Hip Fractures

Abstract: A significantly larger proportion of older patients with hip fractures had osteoporosis, helping validate the utility of CT attenuation in this context. In addition, a large proportion of these patients already had these images available, thus potentially helping limit cost and unnecessary medical investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The 3D models of the femoral head were imported into the 3-Matic Medical 13.0, a 3D model processing software, to create uniform and volume mesh. Then, the mesh models of the femoral head were imported back into the Mimics software, and the calculation of bone mineral density (BMD) was conducted according to the experience formula method reported in previous studies [23,24].…”
Section: Ct Images Analysismentioning
confidence: 99%
“…The 3D models of the femoral head were imported into the 3-Matic Medical 13.0, a 3D model processing software, to create uniform and volume mesh. Then, the mesh models of the femoral head were imported back into the Mimics software, and the calculation of bone mineral density (BMD) was conducted according to the experience formula method reported in previous studies [23,24].…”
Section: Ct Images Analysismentioning
confidence: 99%
“…The use of fenestrated implants allows to perform the augmentation procedure through the implant, providing the ability to first make a clinical judgement of the local bone quality when inserting the head element. Although BMD measurements are recommended for patients at risk of fractures, they are rarely performed and patients come in with their fractures without objective measurement of the underlying osteoporosis (Boonen S., 2011 andEmohare O., 2015). As reported in a previous study on cement augmentation of cadaveric bones, the feasibility of augmentation depends on the local quality of the bone surrounding the head element and augmentation is most effective in osteoporotic bone (Sermon, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies on opportunistic CT have used fractures as outcomes [67][68][69][70][71][72][73][74]. In patients who had a hip fracture after an abdominopelvic CT examination performed for other reasons, Lee et al [73] reported significantly lower L1 trabecular attenuation values (98.5 ± 36.8 HU) in patients who fractured, compared to age-and sex-matched controls (129.7 ± 44.9 HU).…”
Section: The Presentmentioning
confidence: 99%